Reproductive cycle progression arrest and modification of cell morphology (shape and biovolume) in the alga Pseudokirchneriella subcapitata exposed to metolachlor - Machado, Maria Manuela Dias (2020)
Supplementary material related to this article can be found, in the online version, at doi:https://doi.org/10.1016/j.aquatox.2020.105449.